Esophageal Trauma: Analysis of Incidence, Morbidity, and Mortality. Issue 10 (October 2019) - Gambhir, Sahil; Grigorian, Areg; Swentek, Lourdes; Maithel, Shelley; Sheehan, Brian M.; Daly, Shaun; Lekawa, Michael; Nahmias, Jeffry
Traumatic esophageal injury is a highly lethal but rare injury with minimal data in the trauma population. We sought to provide a descriptive analysis of esophageal trauma (ET) to identify the incidence, associated injuries, interventions, and outcomes. We hypothesized that blunt trauma is associated with higher risk of death than penetrating trauma. The Trauma Quality Improvement Program (2010–2016) was queried for patients with ET. Patients with blunt and penetrating trauma were compared using chi-square and Mann-Whitney U tests. A multivariable logistic regression model was used to determine risk of mortality. Of 1, 403, 466 adult patients, 651 (<0.01%) presented with ET. The most common associated thoracic injuries were rib fractures (38.7%) and pneumothorax (26.7%). More patients with a penetrating mechanism underwent open repair of the esophagus than those with blunt mechanism (46.2% vs 11.7%, P < 0.001). After controlling for covariates, there was no difference in risk of mortality between blunt and penetrating trauma ( P = 0.65). The mortality rate for patients with esophageal injury surviving greater than 24 hours was 7.5 per cent. In this large national database analysis, ET was rare and most commonly associated with rib fractures and pneumothorax. Contrary to our hypothesis, the risk of mortality was equivalent between blunt and penetrating ET.